Effects of weight divisions in time-motion of female high-level Brazilian Jiu-jitsu combat behaviors - Santos, Marco Antonio Ferreira dos; Soto, Dany Alexis Sobarzo; de Brito, Michele Andrade; Brito, Ciro José; Aedo-Muñoz, Esteban; Slimani, Maamer; Bragazzi, Nicola L.; Znazen, Hela; Miarka, Bianca (Frontiers in Psychology, 2023)
Coaches and psychologists can use time-motion analysis to elaborate specific interventions for female BJJ athletes, increasing specific training context and reducing unnecessary psychological and physical demands and injuries. Therefore, the present study aimed to analyze high-level BJJ female athletes in the 2020 Pan-American Games by comparing the weight categories on the time-motion analysis. The time-motion analysis (i.e., approach, gripping, attack, defensive actions, transition, mounting, guard, side control, and submissions) of 422 high-level female BJJ combats was divided and compared by weight category as follows: Rooster (n = 8), Light Feather (n = 18), Feather (n = 122), Light (n = 84), Middle (n = 74), Medium Heavy (n = 44), Heavy (n = 36), Super Heavy (n = 36), using p ≤ 0.05. The main results indicated that the Super heavyweight category [3.1 (5.8;119.9) s] had a shorter gripping time than other weight categories, p ≤ 0.05. In contrast, roosters [7.2 (3.5;64.6) s] had longer gripping, transition [14.0 (4.8;29.6) s], and attack time [76.2 (27.7, 93.2)] than the light feather, middlers, and heavier weight categories, p ≤ 0.05. These findings should be considered for the psychological interventions and training prescription.